Polyacrylamide suitable for oilfield reinjection sewage preparation and preparation process thereof

By introducing sulfobetaine acrylamide and long-chain alkyl acrylamide monomers, combining with polyethylene glycol, optimizing the polymerization process, and forming a hydrophobic associating network structure, the viscosity attenuation and solubility and dispersion problems of polyacrylamide in high-temperature and high-salt oilfield environments were solved, and efficient oil recovery in complex oil reservoirs was achieved.

CN120737252APending Publication Date: 2025-10-03HENAN ZHENGJIA ENERGY ENVIRONMENTAL PROTECTION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510895353.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-30
Publication Date
2025-10-03

AI Technical Summary

Technical Problem

Existing polyacrylamide is easily hydrolyzed, its molecular chains curled, and precipitated in the high-temperature and high-salt environment of oil fields, resulting in viscosity attenuation. It cannot be effectively applied to complex oil reservoirs. In addition, it has poor solubility and dispersibility during on-site preparation, making it difficult to meet oil recovery efficiency requirements.

Method used

Sulfobetaine acrylamide monomers and long-chain alkyl acrylamide monomers are used in combination with polyethylene glycol as an auxiliary agent to optimize the polymerization process parameters to form a hydrophobic associating network structure, thereby improving shear stability and solubility and dispersibility.

Benefits of technology

It maintains good viscosity in high-temperature and high-salt environments, achieves low-concentration thickening, rapid dissolution and uniform dispersion, improves the oil displacement efficiency and on-site preparation efficiency of the polymer, and solves the problem of insufficient application of polymers in complex oil reservoirs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120737252A_ABST
    Figure CN120737252A_ABST
Patent Text Reader

Abstract

The invention relates to the field of oilfield chemicals, and discloses polyacrylamide suitable for oilfield reinjection sewage preparation and a preparation process thereof, the composition comprises the following components by mass: 74-78% of an acrylamide monomer, 10-20% of an initiator, 10-20% of an initiator, 10-20% of a crosslinking agent, 1-3% of a crosslinking agent, 1-3% of a crosslinking agent, 1-3% of a crosslinking agent, and the balance of water. 12%-16% of a 2-acrylamide-2-methyl propane sulfonic acid monomer; 0.1%-3% of a sulfobetaine type acrylamide monomer; 0.05% to 0.5% of a long-chain alkyl acrylamide monomer; the total addition amount of the initiator accounts for 0.1%-0.14% of the total mass of the monomers; the adding amount of the stabilizer accounts for 0.02%-0.04% of the total mass of the monomers; and the balance of deionized water. The sulfobetaine type acrylamide monomer is adopted, so that the polymer can still maintain good viscosity retention ability and solution stability under the condition of extremely high salinity, especially under the condition of a complex stratum with high content of high-valence metal ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemicals, in particular to polyacrylamide suitable for preparing oilfield reinjection wastewater and a preparation process thereof. Background Art

[0002] Against the backdrop of dwindling global oil resources, enhanced oil recovery (EOR) has become crucial for the sustainable development of the oil and gas industry. Polymer flooding technology, in particular, has attracted considerable attention due to its ability to effectively reduce the oil-water mobility ratio, expand the swept volume, and thus significantly increase crude oil recovery. In the development and application of polymer flooding agents, polyacrylamide (PAM) and its derivatives are widely used in oilfield reinjection wastewater preparation and chemical flooding due to their excellent water solubility, thickening ability, and ability to regulate the oil-water interface.

[0003] However, in actual oilfield applications, the amide groups on the existing polyacrylamide polymer chains are susceptible to hydrolysis under high temperatures and salt conditions to form carboxyl groups, resulting in a negatively charged polymer. High-valent cations form strong ionic bridges with these negatively charged groups, causing the polymer chains to curl, aggregate, and even precipitate, significantly reducing their hydrodynamic volume. This loss of viscosity manifests itself as a significant decrease in viscosity. This loss of viscosity directly impairs the ability to control the polymer solution's viscosity, leading to a significant decrease in oil recovery efficiency and severely limiting the application of polymer flooding technology in complex reservoirs. Summary of the Invention

[0004] In response to the shortcomings of the existing technology, the present invention provides a polyacrylamide suitable for the preparation of oilfield reinjection wastewater and its preparation process, which solves the problems of poor temperature and salt resistance of existing polyacrylamide in the complex high-temperature and high-salt environment of the oilfield, insufficient mechanical shear stability during the injection process, poor solubility and dispersibility during on-site preparation, and easy formation of "fish eyes".

[0005] To achieve the above objectives, the present invention is implemented by the following technical solution: a polyacrylamide composition suitable for the preparation of oilfield reinjection wastewater, the composition comprising the following components, the composition comprising the following components, and the mass fraction of each component accounts for the mass percentage of the composition: Acrylamide monomer: 74%-78%; 2-Acrylamide-2-methylpropanesulfonic acid monomer: 12%-16%; Sulfobetaine acrylamide monomer: 0.1%-3%; Long chain alkyl acrylamide monomer: 0.05%-0.5%; Initiator, the total amount of which accounts for 0.1%-0.14% of the total weight of the monomer; Stabilizer, the addition amount accounts for 0.02%-0.04% of the total monomer mass; The balance was deionized water.

[0006] Preferably, the sulfobetaine acrylamide monomer is [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide.

[0007] Preferably, the long-chain alkyl acrylamide monomer is octadecyl acrylamide or other long-chain alkyl acrylamide monomers having a carbon chain length of C 12 -C 22 of alkyl acrylamide.

[0008] Preferably, the initiator is an ammonium persulfate-sodium bisulfite redox system, wherein the mass ratio of ammonium persulfate to sodium bisulfite is 1:1-1:2.

[0009] Preferably, the stabilizer is disodium edetate.

[0010] Preferably, the composition further comprises polyethylene glycol, the content of which accounts for 0.2%-0.4% of the total mass of the final product.

[0011] A method for preparing polyacrylamide suitable for preparing oilfield reinjection wastewater comprises the following steps: a. The acrylamide monomer, 2-acrylamide-2-methylpropanesulfonic acid monomer, sulfobetaine acrylamide monomer and long-chain alkyl acrylamide monomer were dissolved in deionized water and a stabilizer was added; b. Deoxygenating the above monomer solution with nitrogen; c. Add the initiator to the deoxygenated monomer solution at 30-50°C and react for 4-6 hours; d. Cooling and converting the polymerization product.

[0012] Preferably, the pH value of the monomer solution in step a is adjusted to 6.5-7.5.

[0013] Preferably, the flow rate of nitrogen deoxygenation in step b is 0.5-2.0 L / min, and the deoxygenation time is 30-60 minutes.

[0014] Preferably, in the step c, the polymerization reaction temperature is 35-45° C., the initiator is added dropwise for 5-15 minutes, and the polymerization reaction is followed by aging for 0.5-1 hour. In the step d, polyethylene glycol is added after cooling.

[0015] The present invention provides a polyacrylamide suitable for preparing oilfield reinjection wastewater and its preparation process, which has the following beneficial effects: 1. This invention utilizes sulfobetaine acrylamide monomers, enabling the polymer to maintain excellent viscosity retention and solution stability even in complex formations with extremely high salinity, high concentrations of high-valent metal ions, and high temperatures. This solution addresses the shortcomings of existing polyacrylamides, which suffer from significant performance degradation and limited application in such harsh environments.

[0016] 2. The present invention incorporates long-chain alkyl acrylamide monomers, enabling polyacrylamide to form a hydrophobic associating network structure in aqueous solution. This structure achieves a thickening effect at relatively low polymer concentrations and exhibits shear-thinning rheological properties, overcoming the drawback of traditional polyacrylamide, which requires a higher dosage to achieve the same viscosity, leading to increased costs.

[0017] 3. The present invention adds polyethylene glycol as an auxiliary agent during the preparation process, which improves the wettability and dispersion characteristics of the polyacrylamide product in water. This enables the product to dissolve quickly and evenly during on-site preparation, avoiding the problems of slow dissolution and easy agglomeration to form "fish eyes" of traditional polyacrylamide powder, thereby improving on-site preparation efficiency.

[0018] 4. By optimizing the monomer structure (comprising sulfobetaine acrylamide monomers and long-chain alkyl acrylamide monomers) and controlling polymerization process parameters, the polyacrylamide of the present invention exhibits excellent resistance to mechanical shear degradation. Compared to existing polyacrylamides, which suffer from a significant drop in viscosity after high-intensity pumping and long-distance pipeline transportation, the polymer of the present invention is able to better maintain molecular chain integrity, ensuring that its viscosity is effectively maintained during oilfield injection. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the process steps of the present invention; Figure 2 This is a comparison table of the viscosity and viscosity retention of polyacrylamide of Example 1 of the present invention and Comparative Example 1 under different aging conditions; Figure 3 This is a comparison table of apparent viscosities of polyacrylamide of Example 2 of the present invention and Comparative Example 2 at different concentrations and shear rates; Figure 4 This is a comparison table of the solubility and dispersion properties of polyacrylamide in Example 3 of the present invention and Comparative Example 3; Figure 5 This is a comparison table of viscosity loss rates of polyacrylamide in Example 1, Example 2 and Comparative Example 2 of the present invention under different shear conditions. DETAILED DESCRIPTION

[0020] The following will clearly and completely describe the technical solution of the present invention in conjunction with the accompanying drawings. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0021] Please see the attached Figure 1 The embodiment of the present invention provides a polyacrylamide composition suitable for preparing oilfield reinjection wastewater, the composition comprising the following components, and the mass fraction of each component accounts for the mass percentage of the total monomers: Acrylamide monomer: 74%-78%; 2-Acrylamide-2-methylpropanesulfonic acid monomer: 12%-16%; Sulfobetaine acrylamide monomer: 0.1%-3%; Sulfobetaine acrylamide monomer is [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide.

[0022] Long-chain alkyl acrylamide monomer: 0.05%-0.5%; long-chain alkyl acrylamide monomer is octadecyl acrylamide or other carbon chain length C 12 -C 22 of alkyl acrylamide.

[0023] The total amount of the initiator added is 0.1%-0.14% of the total weight of the monomer; the initiator is an ammonium persulfate-sodium bisulfite redox system, wherein the mass ratio of ammonium persulfate to sodium bisulfite is 1:1-1:2.

[0024] Stabilizer, the addition amount of which accounts for 0.02%-0.04% of the total weight of the monomer. The stabilizer is disodium ethylenediaminetetraacetic acid.

[0025] Polyethylene glycol, whose content accounts for 0.2%-0.4% of the total mass of the final product; The balance was deionized water.

[0026] A method for preparing polyacrylamide suitable for preparing oilfield reinjection wastewater comprises the following steps: a. dissolving acrylamide monomer, 2-acrylamide-2-methylpropanesulfonic acid monomer, sulfobetaine acrylamide monomer and long-chain alkyl acrylamide monomer in deionized water and adding a stabilizer; the pH value of the monomer solution in step a is adjusted to 6.5-7.5.

[0027] b. The above monomer solution was subjected to nitrogen deoxygenation treatment; the flow rate of nitrogen deoxygenation in step b was 0.5-2.0 L / min, and the deoxygenation time was 30-60 minutes.

[0028] c. Adding an initiator to the deoxygenated monomer solution at 30-50 ° C and reacting for 4-6 hours; the polymerization temperature in step c is 35-45 ° C, the initiator is added for 5-15 minutes, and the polymerization reaction is heated and matured for 0.5-1 hour; d. Cooling and converting the polymerization reaction product, adding polyethylene glycol after cooling in step d.

[0029] Example 1: Preparation of high temperature-resistant and salt-resistant polyacrylamide: This example aims to prepare a polyacrylamide that can maintain excellent performance in a high-temperature and high-salt environment, focusing on the performance improvement brought by the sulfobetaine acrylamide monomer.

[0030] Composition composition: Acrylamide monomer: 74g (74% of the total monomer mass); 2-Acrylamide-2-methylpropanesulfonic acid monomer: 12g (12% of the total monomer mass); Sulfobetaine acrylamide monomer: [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide: 0.1g (0.1% of the total monomer mass); Long-chain alkyl acrylamide monomer: 0.05 g (0.05% of the total monomer mass); Initiator: ammonium persulfate and sodium bisulfite, total mass 0.1g (0.1% of the total monomer mass); Stabilizer: disodium ethylenediaminetetraacetic acid, 0.02g (0.02% of the total monomer mass); Polyethylene glycol (PEG-6000): 0.2g (0.2% of the total mass of the final product); The balance is deionized water, which is used to prepare the aqueous solution; Preparation steps: Monomer Mixing and Dissolution: First, add the predetermined amount of deionized water to a reaction vessel equipped with a mechanical stirrer and temperature control. Then, slowly add precisely weighed monomers (AM-acrylamide, AMPS-2-acrylamido-2-methylpropanesulfonic acid, DMAPS-[2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide), and SAA-long-chain alkyl acrylamide) to the deionized water. Stir at approximately 100 rpm to ensure complete dissolution of all monomers, forming a transparent, uniform monomer solution.

[0031] Stabilizer Addition and pH Adjustment: After the monomer is completely dissolved, add EDTA-2Na (ethylenediaminetetraacetic acid disodium) to the monomer solution and continue stirring for approximately 30 minutes to ensure complete dissolution of the stabilizer. Next, adjust the pH of the monomer solution to 7.0 using a dilute NaOH solution. This entire process should be performed slowly, and the pH should be continuously monitored for accuracy.

[0032] Deoxygenation: After pH adjustment, high-purity nitrogen protection was initiated. Nitrogen was continuously introduced into the reactor at a rate of 1.2 L / min for 45 minutes to deoxygenate the solution. This step was intended to reduce the dissolved oxygen in the solution to a minimum, creating favorable conditions for the subsequent polymerization reaction.

[0033] Initiation and Polymerization: Under nitrogen protection and continuous stirring, raise the reactor temperature to 40°C and maintain this temperature precisely. Simultaneously, prepare the APS (aminoammonium persulfate) solution and the SHS (hydrogen sulfide) solution. Once the system temperature stabilizes, slowly add the two initiator solutions dropwise to the reactor using a constant-speed pump over a 10-minute addition period. After the initiator addition is complete, continue the reaction at 40°C for 5 hours. During this time, closely monitor changes in the system viscosity.

[0034] Heat aging and PEG-polyethylene glycol addition: After the polymerization reaction is complete, continue aging at 40°C for 0.5 hours to ensure complete reaction. Then, stop heating and cool the reactor to room temperature (approximately 25°C). Once the system has cooled, add 0.2g of PEG-6000 and continue stirring for 20 minutes to ensure uniform dispersion.

[0035] Product Preparation: The resulting product is a high-viscosity polyacrylamide hydrogel. Depending on the application requirements, the gel can be cut into pieces, dried in a forced-air oven at 70°C for 18 hours to a constant weight, and then crushed and sieved to obtain a solid powder product.

[0036] Comparative Example 1: This comparative example is intended to be compared with Example 1, the difference being that the polyacrylamide does not contain a sulfobetaine-type monomer (based on a traditional formula), highlighting the unique contribution of the sulfobetaine-type acrylamide monomer to the temperature and salt resistance of the polymer.

[0037] Composition composition: Acrylamide (AM) monomer: 74g; 2-Acrylamido-2-methylpropanesulfonic acid (AMPS) monomer: 12g; Long chain alkyl acrylamide (SAA) monomer: 0.05g; Initiator: ammonium persulfate and sodium bisulfite, total mass 0.1g (0.14% of the total monomer mass); Stabilizer: disodium ethylenediaminetetraacetic acid, 0.02g (0.02% of the total monomer mass); Polyethylene glycol (PEG-6000): 0.2g (0.2% of the total mass of the final product); The balance is deionized water, which is used to prepare the aqueous solution; Preparation steps: The preparation steps were essentially the same as those in Example 1, with the primary difference being that DMAPS-[2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide monomer was not added during the monomer mixing step. All other process parameters, such as stirring speed, pH adjustment, deoxygenation conditions, reaction temperature, initiator addition method, and post-processing steps, remained identical to those in Example 1.

[0038] Example 2: Preparation of highly efficient hydrophobically associating polyacrylamide: This example aims to prepare a polyacrylamide that can achieve a significant thickening effect at a low concentration, focusing on the hydrophobic associative thickening effect brought about by the long-chain alkyl acrylamide monomer.

[0039] Composition composition: Acrylamide monomer: 76g (76% of the total monomer mass); 2-Acrylamide-2-methylpropanesulfonic acid monomer: 14g (14% of the total monomer mass); Sulfobetaine acrylamide monomer: [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide: 1.5g (1.5% of the total monomer mass); Long-chain alkyl acrylamide monomer: 0.25 g (0.25% of the total monomer mass); Initiator: ammonium persulfate and sodium bisulfite, total mass 0.7g (0.7% of the total monomer mass); Stabilizer: disodium ethylenediaminetetraacetic acid, 0.03g (0.03% of the total monomer mass); The balance is deionized water, which is used to prepare the aqueous solution; Polyethylene glycol (PEG-4000): 0.3g (0.3% of the total mass of the final product) Preparation steps: Monomer Dissolution: Add deionized water to a reaction kettle, followed by AM (acrylamide), AMPS (2-acrylamide-2-methylpropanesulfonic acid), DMAPS (2-(methacryloyloxy)ethyl)dimethyl-(3-sulfonic acid propyl) ammonium hydroxide), and SAA (long-chain alkyl acrylamide monomer). Stir at 120 rpm to ensure complete dissolution of the monomers.

[0040] Stabilizer and pH: Add EDTA-2Na-ethylenediaminetetraacetic acid disodium and stir for 25 minutes to adjust the pH of the solution to 7.5.

[0041] Deoxygenation: The monomer solution was deoxygenated at a nitrogen flow rate of 1.0 L / min for 50 minutes.

[0042] Polymerization: Set the reaction temperature to 35°C. Prepare the APS (aminopersulfate) solution and the SHS (hydrogen sulfide) solution separately. Slowly add the initiator solution dropwise over 8 minutes. Continue the reaction at 35°C for 6 hours.

[0043] Post-treatment: After the reaction is complete, heat and mature at the same temperature for 1 hour. After cooling to room temperature (approximately 22°C), add 0.3g of PEG-4000 (polyethylene glycol) and continue stirring for 15 minutes. The resulting product is a high-viscosity hydrogel.

[0044] Comparative Example 2: This comparative example is intended to be compared with Example 2, the difference being that the polyacrylamide does not contain long-chain alkyl acrylamide, highlighting the role of long-chain alkyl acrylamide monomers in low-concentration thickening and hydrophobic association.

[0045] Composition composition: Acrylamide (AM) monomer: 76g (76% of the total monomer mass); 2-Acrylamido-2-methylpropanesulfonic acid (AMPS) monomer: 14 g (14% of the total monomer mass); [2-(Methacryloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide (DMAPS) monomer: 1.5 g (1.5% of the total monomer weight); Initiator: ammonium persulfate and sodium bisulfite, total mass 0.7g (0.7% of the total monomer mass); Stabilizer: disodium ethylenediaminetetraacetic acid, 0.03g (0.03% of the total monomer mass); Polyethylene glycol (PEG-4000): 0.3 g (0.3% of the total mass of the final product); The balance is deionized water, which is used to prepare the monomer aqueous solution; Preparation steps: The preparation steps were identical to those in Example 2, with the key difference being that no SAA (long-chain alkyl acrylamide) monomer was added during the monomer mixing step. The total monomer mass remained unchanged, and all other process parameters, such as stirring speed, pH adjustment, deoxygenation, reaction temperature, initiator addition method, and post-treatment, remained consistent with those in Example 2.

[0046] Example 3: Preparation of high dissolution efficiency polyacrylamide: This example aims to prepare a polyacrylamide with fast dissolution rate and good dispersibility, focusing on the effect of polyethylene glycol in improving the solubility and dispersibility of the product.

[0047] Composition composition: Acrylamide monomer: 78g (78% of the total monomer mass); 2-Acrylamide-2-methylpropanesulfonic acid monomer: 16g (16% of the total monomer mass); Sulfobetaine acrylamide monomer: [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide: 3.0g (3% of the total monomer mass); Long-chain alkyl acrylamide monomer: 0.5 g (0.5% of the total monomer mass); Initiator: ammonium persulfate and sodium bisulfite, total mass 0.14g (0.14% of the total monomer mass); Stabilizer: disodium ethylenediaminetetraacetic acid, 0.04g (0.04% of the total monomer mass); Polyethylene glycol (PEG-4000): 0.4 g (0.4% of the total mass of the final product); The balance is deionized water, which is used to prepare the aqueous solution; Preparation steps: Monomer mixing and dissolution: Add deionized water to a reaction kettle, followed by AM (acrylamide), AMPS (2-acrylamide-2-methylpropanesulfonic acid), DMAPS (2-(methacryloyloxy)ethyl)dimethyl-(3-sulfonic acid propyl) ammonium hydroxide, and SAA (long-chain alkyl acrylamide monomer). Stir at 80 rpm to ensure uniform dissolution of the monomers.

[0048] Stabilizer and pH: Add EDTA-2Na-ethylenediaminetetraacetic acid disodium and stir for 35 minutes to adjust the solution pH to 6.8.

[0049] Deoxygenation: The nitrogen flow rate was set to 1.5 L / min and the deoxygenation time was 40 minutes.

[0050] Polymerization: Raise the reaction temperature to 45°C. Prepare the APS-aminopersulfate solution and the SHS-hydrogen sulfide solution separately. Add both initiator solutions dropwise over 12 minutes. Allow to react at 45°C for 4.5 hours.

[0051] Post-treatment and Timing of PEG-Polyethylene Glycol Addition: After polymerization, heat and age for 0.8 hours. After cooling to room temperature (approximately 20°C), cut the reaction product into pieces and directly dry them (oven drying at 75°C for 20 hours). After the dried solid powder cools to room temperature, evenly spray or mix 0.05g of PEG-8000 (polyethylene glycol) into the polyacrylamide powder, then pulverize and sieve.

[0052] Comparative Example 3: This comparative example is intended to be compared with Example 3, the difference being that the polyacrylamide does not contain polyethylene glycol, highlighting the unique role of polyethylene glycol in improving the solubility and dispersibility of the product.

[0053] Composition composition: Acrylamide (AM) monomer: 78 g (78.0% of the total monomer mass); 2-Acrylamido-2-methylpropanesulfonic acid (AMPS) monomer: 16 g (16.0% of the total monomer mass); [2-(Methacryloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide (DMAPS) monomer: 3g (3% of the total monomer weight); Long-chain alkyl acrylamide monomer: 0.5 g (0.5% of the total monomer mass); Initiator: ammonium persulfate and sodium bisulfite, total mass 0.14g (0.14% of the total monomer mass); Stabilizer: disodium ethylenediaminetetraacetic acid, 0.04g (0.04% of the total monomer mass); The balance is deionized water, which is used to prepare the aqueous solution; The preparation steps were identical to those in Example 3, with the key difference being that polyethylene glycol (PEG) was not added during the post-treatment step. All other process parameters, such as monomer mixing, pH adjustment, deoxygenation, reaction temperature, initiator addition method, polymerization reaction time, and drying conditions, remained the same as in Example 3.

[0054] To validate the technical effectiveness of the polyacrylamide composition and its preparation process described herein for the preparation of oilfield reinjection wastewater, we designed the following series of comparative experiments. These experiments aimed to quantify the improvements in key properties of the polyacrylamide described herein, such as temperature and salt resistance, hydrophobic association thickening, solubility and dispersibility, and shear stability, and to compare them with conventional technologies.

[0055] Experiment 1: Evaluation of Polyacrylamide's Heat and Salt Resistance—Detailed Description and Results Analysis This experiment aimed to accurately evaluate the viscosity retention of the polyacrylamide prepared according to the present invention (Example 1) under the harsh environment of oilfield reinjection water, and to directly compare it with a traditional formulation (Comparative Example 1). The key focus was on whether the introduction of sulfobetaine acrylamide monomers could significantly improve the stability of the polymer under high-temperature and high-salinity conditions, thereby effectively addressing the prominent problem of polymer performance degradation in existing technologies.

[0056] Experimental methods and settings: Preparation of simulated formation water: A highly mineralized simulated formation water was carefully prepared, with a total mineralization of 250,000 mg / L to accurately reflect the complex ionic environment found in oilfield reinjection water. The specific composition and ratios were: 150,000 mg / L sodium chloride (NaCl), 60,000 mg / L calcium chloride dihydrate (CaCl2·2H2O), and 40,000 mg / L magnesium chloride hexahydrate (MgCl2·6H2O). All salts were analytical grade, accurately weighed, dissolved in deionized water, and thoroughly stirred.

[0057] Polymer solution preparation: Weigh 2.00 g of each of the polyacrylamide solid powders prepared in Example 1 and Comparative Example 1.

[0058] Sprinkle the weighed powder slowly and evenly into 1000 mL of prepared simulated formation water.

[0059] The solution was stirred at 300 rpm using a magnetic stirrer at 25°C for 2 h until the polymer was completely dissolved to form a homogeneous solution with a concentration of 2,000 mg / L.

[0060] After preparation, the two polymer solutions were allowed to stand for 2 hours to ensure that the molecules were fully stretched.

[0061] Viscosity measurement and aging: Initial viscosity: Measure the initial apparent viscosity of the polymer solutions of Example 1 and Comparative Example 1 at 25°C using a Brookfield DV2T rotational viscometer (using a suitable rotor, such as UL or SC4-18) at a speed of 6 rpm, and record the data.

[0062] Dynamic aging: Take 100mL of polymer solution and pour it into 200mL high-pressure stainless steel aging kettles. Pass high-purity nitrogen into the aging kettle for 30 minutes to completely remove dissolved oxygen and avoid oxidative degradation. Seal the aging kettle to ensure there is no leakage. Place the aging kettle in a constant temperature oven with a preset temperature of 90°C for dynamic aging, and the aging time is set to 7 days. Every 24 hours, take out the aging kettle, quickly cool it to 25°C in a cold water bath, open the lid to take a sample, measure its apparent viscosity and record it. After the measurement is completed, reseal the remaining solution and continue aging.

[0063] Static Aging: Pour 100 mL of polymer solution into a separate 250 mL Erlenmeyer flask. Seal the flask with plastic wrap and secure with a rubber band, ensuring some headroom. Place the flask in a constant-temperature water bath at 80°C for static aging for the same 7 days. Remove the sample daily at a fixed time (e.g., 9:00 AM), cool to 25°C, and measure and record the apparent viscosity.

[0064] Data processing: Based on the measured viscosity data, the viscosity retention rate of the polymer solution at different aging time points was calculated, that is, viscosity retention rate (%) = (viscosity after aging / initial viscosity) × 100%.

[0065] See attached Figure 2 : Comparison of viscosity and viscosity retention of polyacrylamide in Example 1 and Comparative Example 1 under different aging conditions: Experimental results and mechanism analysis: It can be clearly seen from the above simulation experimental data that in the aging test of the simulated high-temperature and high-mineralization formation water in the oil field, the viscosity retention rate of the polyacrylamide prepared in Example 1 is significantly better than that of Comparative Example 1 throughout the entire aging cycle, both under dynamic and static conditions.

[0066] The viscosity of Comparative Example 1 decays rapidly and dramatically in a high-temperature and high-salt environment, which fully exposes the inherent defects of traditional polyacrylamide in that its molecular chains are prone to curling, precipitation, and even degradation under high salinity and high-temperature conditions, resulting in a significant reduction in its thickening ability and an inability to meet the needs of actual oilfield applications.

[0067] The key to this invention's remarkable heat and salt resistance lies in the ingenious introduction of a sulfobetaine acrylamide monomer. This monomer possesses a unique zwitterionic structure, meaning both anionic and cationic groups coexist within a single molecule. In the harsh environment of high temperature and high salt concentrations, particularly in the presence of high-valent metal ions, the anionic groups of traditional polyacrylamides (such as those containing AMPS) readily form "bridging" interactions with multivalent cations, causing molecular chain contraction, association, and precipitation, resulting in loss of water solubility and thickening ability.

[0068] However, the zwitterionic properties of sulfobetaine monomers enable them to form a stable "inner salt" structure in saline solutions, effectively shielding the negative effects of external high-valent cations on their molecular chains, greatly enhancing the rigidity of the polymer chain and its anti-electrolyte shielding effect. This inherent stability allows the polymer to maintain an extended conformation in high-salt systems, thereby maintaining its high viscosity.

[0069] Therefore, the excellent viscosity retention of the polyacrylamide in Example 1 under high-temperature, high-salinity conditions is not accidental, but rather an intrinsic property of its unique molecular structure. This performance improvement directly addresses the long-standing limitation of existing polyacrylamide applications in high-temperature, high-mineralization reservoirs, providing strong chemical support for the development of more complex and deeper oil and gas resources.

[0070] Experiment 2: Evaluation of the Hydrophobic Association Thickening and Shear Thinning Properties of Polyacrylamide - Detailed Description and Results Analysis The core objective of this experiment was to further explore the ability of the polyacrylamide prepared in Example 2 to achieve significant thickening at relatively low concentrations, as well as its unique shear-thinning rheological properties. By comparing this with Comparative Example 2, which does not contain long-chain alkyl acrylamide, the goal was to clarify the critical contribution of hydrophobic association to polymer performance, which is crucial for optimizing oilfield chemical flooding efficiency and reducing operating costs.

[0071] Preparation of simulated formation water: To effectively simulate the actual saline environment of the oilfield and ensure the full potential of hydrophobic association, simulated formation water with a total mineralization of 50,000 mg / L was prepared. Its components included 40,000 mg / L of sodium chloride (NaCl) and 10,000 mg / L of calcium chloride dihydrate (CaCl2·2H2O). All reagents were of analytical grade, accurately weighed, dissolved in deionized water, and thoroughly stirred.

[0072] Polymer solution preparation: The polyacrylamide solid powders of Example 2 and Comparative Example 2 were weighed.

[0073] Each sample was prepared into a polymer solution with two concentrations of 1,000 mg / L and 1,500 mg / L in the above-mentioned simulated formation water.

[0074] All solutions were stirred at 250 rpm for 3 h at 25 °C using a magnetic stirrer to ensure that the polymers were fully dissolved and the molecular chains were fully stretched.

[0075] Rheological properties test: Viscosity-Concentration Relationship: The apparent viscosities of the four polymer solutions were measured at 25°C using a Brookfield DV2T rotational viscometer (using either an UL or SC4-18 spindle) at 6 rpm. This was done to directly quantify the thickening performance of Example 2 and Comparative Example 2 at the same concentration.

[0076] Shear thinning curves: Shear rate sweep tests were conducted on the polymer solutions of Example 2 and Comparative Example 2 at a concentration of 1,500 mg / L using a HAAKE MARS60 high-precision rotational rheometer. The test temperature was set at 25°C.

[0077] Shear rate range from 0.1S -¹ Gradually increase to 100S according to the logarithmic length -¹ During this process, the apparent viscosity at each shear rate was recorded in real time.

[0078] Data Analysis: Based on the measured viscosity data and rheological curves, a direct comparison of the thickening performance of Example 2 and Comparative Example 2 at different concentrations was conducted. The shear thinning behavior was analyzed in particular. By plotting the viscosity versus shear rate, the rheological characteristics of the two polymers were quantified and evaluated.

[0079] Refer to the attached Figure 3 : Comparison of apparent viscosity of polyacrylamide in Example 2 and Comparative Example 2 at different concentrations and shear rates: Experimental results and mechanism analysis: The simulation experimental data directly reveals the significant performance advantages of the polyacrylamide of the present invention. At a concentration of 1000 mg / L, the polymer prepared in Example 2 exhibits an apparent viscosity much higher than that of Comparative Example 2.

[0080] When the concentration is increased to 1500 mg / L, the thickening efficiency of Example 2 is almost twice that of Comparative Example 2. This directly challenges the conventional wisdom that high polymer concentrations are required to achieve ideal thickening effects, highlighting the enormous economic potential of this invention. This remarkable thickening ability stems from the long-chain alkyl acrylamide monomers introduced in this invention. These sulfur-water groups exhibit a tendency to spontaneously aggregate in aqueous environments. When incorporated as comonomers into the polymer backbone, these hydrophobic domains no longer exist in isolation, but instead form a dynamically reversible "sulfur-water association network" through intermolecular and intramolecular hydrophobic interactions.

[0081] This network significantly increases the effective volume and topological entanglement of the polymer molecular chains, thereby significantly improving the macroscopic viscosity of the solution. In contrast, the thickening ability of Comparative Example 2, which lacks such an internal network, is naturally limited.

[0082] Furthermore, the shear-thinning curve shows that Example 2 exhibits a more pronounced decrease in viscosity as the shear rate increases, demonstrating superior shear-thinning rheological properties. This property is crucial for oilfield flooding: in high-shear areas such as injection lines and near-wellbore areas, polymer viscosity decreases as shear forces increase, helping to reduce pumping pressure and ensure smooth injection.

[0083] However, once it enters the low-shear region of the reservoir's pore glands, its viscosity quickly recovers, effectively expanding the swept volume and improving oil displacement efficiency. This is undoubtedly a powerful breakthrough in addressing the rheological deficiencies of existing polymers, enabling the present invention to demonstrate greater operational convenience and overall economic efficiency in actual oilfield applications.

[0084] Experiment 3: Evaluation of the Solubility and Dispersion Properties of Polyacrylamide - Detailed Description and Results Analysis This experiment aimed to comprehensively evaluate the solubility and dispersion uniformity of the polyacrylamide prepared in this invention (Example 3) in water and rigorously compare it with Comparative Example 3, which did not contain polyethylene glycol. The core goal was to verify the key role of polyethylene glycol (PEG) as an adjuvant in fundamentally improving the ease of on-site formulation of polymer products, which has direct and significant significance for improving oilfield operational efficiency.

[0085] Experimental methods and settings: Water Sample Preparation: Deionized water is used as the primary preparation water to eliminate the interference of complex ions on solubility and dispersion, thereby more purely examining the polymer's inherent properties. Alternatively, conventional simulated formation water with a total mineralization of 20,000 mg / L, containing 18,000 mg / L of sodium chloride (NaCl) and 2,000 mg / L of calcium chloride dihydrate (CaCl2·2H2O), can be prepared as an auxiliary to simulate the typical environment of actual oilfield applications.

[0086] Preparation of polymer samples: Accurately weigh 0.50 g of the polyacrylamide solid powder of Example 3 and Comparative Example 3, respectively, and ensure that the powder particle size and morphology are as consistent as possible to avoid interference of external factors on the experimental results.

[0087] Dissolution rate test: Standard operation: Place 250 mL of the prepared water sample in a 500 mL glass beaker. Place the beaker on a magnetic stirrer, start the stirring function, and set the stirring speed to 400 rpm.

[0088] Powder addition and timing: Quickly and evenly add 0.50g of pre-weighed polyacrylamide powder to the water surface while stirring. Start timing the moment of addition.

[0089] Macroscopic observation and recording: During the timing process, closely observe the entire process of polymer powder wetting, dispersion, agglomeration ("fish eye" formation) and final dissolution and clarification in the solution.

[0090] Assessment of the number of “fish eyes”: Every 1 minute, observe with the naked eye and record the approximate number of “fish eyes” (incompletely dissolved polymer clumps) visible on the surface or inside the solution.

[0091] Determination of complete dissolution time: Continue observing until the solution is completely clear and transparent, with no visible solid particles or "fish eyes". Stop the timer and record the time required for complete dissolution. Repeat each experiment three times and take the average value.

[0092] Solution uniformity test: After the above dissolution process is completed (or after the preset dissolution time is reached), use a pipette to carefully extract approximately 10 mL of solution samples from different depths of the beaker (for example, 1 cm from the top, middle, and bottom 1 cm).

[0093] The apparent viscosities of the three samples and the standard concentration solution were measured using a Brookfield DV2T rotational viscometer at 25°C and 6 rpm.

[0094] Data Analysis: Calculate the deviation of the sample viscosity at different locations from the average viscosity. Smaller viscosity deviations indicate better polymer dispersion uniformity in the solution. Also, comprehensively compare the complete dissolution time, number of "fisheyes," and solution uniformity of Example 3 and Comparative Example 3 to comprehensively evaluate their dissolution and dispersion properties.

[0095] Please see the attached Figure 4 : Comparison of the solubility and dispersion properties of polyacrylamide in Example 3 and Comparative Example 3; Experimental results and mechanism analysis: Simulation experimental data clearly demonstrate that the polyacrylamide prepared in Example 3 demonstrates overwhelming superiority in solubility and dispersion performance over that of Comparative Example 3. Its average dissolution time is only about one-third that of the comparative example, and the number of "fish-eyes" during the dissolution process is significantly reduced. The resulting solution exhibits excellent uniformity and minimal viscosity deviation. This directly addresses the on-site preparation challenges commonly encountered with existing polyacrylamide products, such as slow dissolution and easy aggregation to form "fish-eyes," significantly improving operational efficiency and convenience.

[0096] The key to achieving such significant solubility improvements in this invention lies in the introduction of polyethylene glycol (PEG). As a hydrophilic polymer, PEG-PEG works in two key ways. First, when evenly distributed as an adjuvant on the surface of polyacrylamide powder particles, it rapidly absorbs water, reducing the interfacial tension on the powder particle surface, significantly promoting the penetration and diffusion of water into the polymer particles. This "wetting" effect allows the polymer particles to be more quickly coated with water molecules, reducing the tendency for particles to agglomerate due to hydrophobic interactions.

[0097] Secondly, PEG-polyethylene glycol effectively inhibits the excessive entanglement of polymer molecular chains in the early stage of dissolution through the steric hindrance effect. After traditional polyacrylamide powder comes into contact with water, the surface will quickly absorb water to form a high-viscosity gel layer. This gel layer hinders the contact between the internal powder particles and water, resulting in the formation of "fish eyes" and a slow dissolution rate. The presence of PEG-polyethylene glycol is equivalent to inserting an "isolation layer" between the polymer chains, preventing the rapid entanglement of the molecular chains and ensuring that water molecules can enter the interior of the particles more smoothly, thereby accelerating the stretching and dissolution of the polymer chains. This synergistic effect enables the polyacrylamide of the present invention to be quickly and evenly dispersed in water, providing convenience for on-site preparation operations in oil fields, reducing manpower and time costs, and having significant practical value.

[0098] Experiment 4: Evaluation of polyacrylamide shear stability - detailed description and results analysis This experiment aimed to accurately evaluate the viscosity loss of the polyacrylamides prepared according to the present invention (Examples 1 and 2) after being subjected to high-intensity mechanical shear, and to compare the results with Comparative Example 2, which does not contain long-chain alkyl acrylamide. The core objective was to verify how the composite monomer structure design and polymerization process control of the present invention effectively enhance the polymer's resistance to mechanical degradation during injection into complex oil fields, thereby ensuring its effectiveness in pipeline transportation and formation displacement.

[0099] Experimental methods and settings: Simulated formation water preparation: Simulated formation water with a total mineralization of 50,000 mg / L was used. Its composition was the same as in Experiment 2: 40,000 mg / L sodium chloride (NaCl) and 10,000 mg / L calcium chloride dihydrate (CaCl2·2H2O). This water sample provides a typical saline environment, allowing for a more realistic simulation of oilfield application conditions.

[0100] Polymer solution preparation: The polyacrylamide solid powders of Example 1, Example 2 and Comparative Example 2 were accurately weighed respectively.

[0101] Each sample was prepared into a 2,000 mg / L polymer solution in the above-mentioned simulated formation water.

[0102] All solutions were stirred at 300 rpm using a magnetic stirrer at 25 °C for 3 h to ensure that the polymers were fully dissolved and the molecular chains were fully stretched to reach equilibrium.

[0103] Initial viscosity measurement: The initial apparent viscosities of the polymer solutions of Example 1, Example 2, and Comparative Example 2 were measured at 25°C using a Brookfield DV2T rotational viscometer (using a suitable rotor, such as UL or SC4-18) at a speed of 6 rpm.

[0104] Cutting process: High-shear pump circulation simulation: 250 mL of polymer solution was injected into a circulation system equipped with a small reciprocating or gear pump (simulating an oilfield injection pipeline) at a pumping rate of 10 mL / min. The solution was continuously sheared within this circulation system for 3 hours. During the circulation process, approximately 20 mL of sample was removed every hour, rapidly cooled to 25°C, and the apparent viscosity was measured and recorded. After the measurement, the remaining solution was reinjected into the circulation system.

[0105] High-speed agitation and shearing: Separately, place 100 mL of polymer solution in a 250 mL beaker. Using a laboratory high-speed shearing machine (e.g., IKAT25 digital Ultra-Turrax) at 10,000 rpm, shear the solution for 15 minutes. This method simulates a localized high-intensity shear environment.

[0106] Post-shear viscosity measurement and calculation: After each shear treatment (pump circulation or high-speed stirring), the apparent viscosity of the polymer solution at 25°C and 6 rpm is measured immediately. Based on the initial viscosity and the post-shear viscosity, the viscosity loss rate is calculated using the following formula: Viscosity loss rate (%) = (initial viscosity – viscosity after shearing) / initial viscosity) × 100%.

[0107] Please see the attached Figure 5 : Comparison of viscosity loss rate of polyacrylamide in Example 1, Example 2 and Comparative Example 2 under different shear conditions; Experimental results and mechanism analysis: The simulation data clearly demonstrates the significant advantages of the polyacrylamide of the present invention in resisting mechanical shear degradation. Whether subjected to high-intensity, high-speed stirring or prolonged pump-circulating shear, the viscosity loss rates of the polymers prepared in Examples 1 and 2 were significantly lower than those of Comparative Example 2. Comparative Example 2 exhibited significant viscosity decay under the same shear conditions, directly confirming the inherent drawback of existing polyacrylamides: their molecular chains are susceptible to breakage and degradation when subjected to high shear forces, significantly impairing their thickening properties.

[0108] The core of this invention's remarkable resistance to mechanical shear degradation lies in the design of the composite monomer structure and the meticulous control of polymerization process parameters. Specifically, the long-chain alkyl acrylamide monomer (as highlighted in Example 2) forms a dynamic hydrophobic association network within the polymer chain. When subjected to shear forces, this network does not directly break like chemical bonds, but instead dissipates energy through the reversible dissociation and recombination of hydrophobic binding sites. This acts as a resilient "buffer system," capable of "self-repairing" or "flexible deformation" under mechanical stress, effectively protecting the polymer backbone and reducing irreversible mechanical fracture.

[0109] In addition, optimization of the polymerization process, such as the selection of the initiator system and precise control of the reaction temperature, ensures that the polymer has a more uniform molecular weight distribution and a more compact chain structure. These factors work together to enable the polyacrylamide molecular chain of the present invention to better maintain its integrity and effective conformation when subjected to mechanical shear, thereby maintaining its thickening activity. This significant improvement in shear resistance is crucial for oilfield polymer injection operations. It ensures that the polymer solution can still maintain sufficient viscosity to enter the reservoir after passing through the polymer injection pump, valves, and long-distance pipeline transportation, achieving efficient oil displacement. This is undoubtedly a key breakthrough in existing polyacrylamide technology.

[0110] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A polyacrylamide composition suitable for preparing oilfield reinjection wastewater, characterized in that: The composition comprises the following components, and the mass fraction of each component accounts for the mass percentage of the composition: Acrylamide monomer: 74%-78%; 2-Acrylamide-2-methylpropanesulfonic acid monomer: 12%-16%; Sulfobetaine acrylamide monomer: 0.1%-3%; Long chain alkyl acrylamide monomer: 0.05%-0.5%; Initiator, the total amount of which accounts for 0.1%-0.14% of the total weight of the monomer; Stabilizer, the addition amount accounts for 0.02%-0.04% of the total monomer mass; The balance was deionized water.

2. The polyacrylamide composition suitable for preparing oilfield reinjection wastewater according to claim 1, characterized in that: The sulfobetaine acrylamide monomer is [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide.

3. The polyacrylamide composition suitable for preparing oilfield reinjection wastewater according to claim 1, characterized in that: The long-chain alkyl acrylamide monomer is octadecyl acrylamide or other long-chain alkyl acrylamide monomers. 12 -C 22 of alkyl acrylamide.

4. The polyacrylamide composition suitable for preparing oilfield reinjection wastewater according to claim 1, characterized in that: The initiator is an ammonium persulfate-sodium bisulfite redox system, wherein the mass ratio of ammonium persulfate to sodium bisulfite is 1:1-1:

2.

5. The polyacrylamide composition suitable for preparing oilfield reinjection wastewater according to claim 1, characterized in that: The stabilizer is disodium edetate.

6. The polyacrylamide composition suitable for preparing oilfield reinjection wastewater according to claim 1, characterized in that: The composition further comprises polyethylene glycol, the content of which accounts for 0.2% to 0.4% of the total mass of the final product.

7. A method for preparing polyacrylamide suitable for preparing oilfield reinjection wastewater, the polyacrylamide composition suitable for preparing oilfield reinjection wastewater according to any one of claims 1 to 6, characterized in that: The following steps are involved: a. The acrylamide monomer, 2-acrylamide-2-methylpropanesulfonic acid monomer, sulfobetaine acrylamide monomer and long-chain alkyl acrylamide monomer were dissolved in deionized water and a stabilizer was added; b. Deoxygenating the above monomer solution with nitrogen; c. Add the initiator to the deoxygenated monomer solution at 30-50°C and react for 4-6 hours; d. Cooling and converting the polymerization product.

8. The method for preparing a polyacrylamide suitable for preparing oilfield reinjection wastewater according to claim 7, characterized in that: The pH value of the monomer solution in step a is adjusted to 6.5-7.

5.

9. The method for preparing a polyacrylamide suitable for preparing oilfield reinjection wastewater according to claim 7, characterized in that: In step b, the flow rate of nitrogen deoxygenation is 0.5-2.0 L / min, and the deoxygenation time is 30-60 minutes.

10. The method for preparing polyacrylamide suitable for preparing oilfield reinjection wastewater according to claim 7, characterized in that: In the step c, the polymerization reaction temperature is 35-45° C., the initiator is added dropwise for 5-15 minutes, and the polymerization reaction is followed by aging for 0.5-1 hour. In the step d, polyethylene glycol is added after cooling.